Improving reading rates and comprehension through audio-assisted extensive reading for beginner learners. (August 2015) - Chang, Anna C.-S.; Millett, Sonia
Abstract: The study investigated the effect of audio-assisted reading on reading rates and comprehension. Sixty-four year-10 secondary EFL students received a treatment of either silent reading (SR) or audio-assisted reading (AR) over a 26-week period for 90 min each week. They read a total of 20 graded readers, 10 at level one and 10 at level two. A pre-test, a post-test, and a three-month delayed post-test were administered to all participants. The test results show that both groups improved their reading rates and their comprehension levels, and the improvement was maintained for up to three months without further treatment. However, the audio-assisted reading group's improvement in reading rates and comprehension levels was substantially higher than for the silent reading group. Reasons for the higher gains of the audio-assisted reading group are explained and pedagogical implications of the study are discussed.